LEYDIG CELL COUNT IS INCREASES IN OLD WISTAR RATS (RATTUS NORVEGICUS) BY ANTIOXIDANT ETHANOL EXTRACT OF MORINGA OLEIFERA (EEMO) - Widiastini, Luh Putu; Karuniadi, I Gusti Agung Manik (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Oxidative stress is the result of an imbalance between antioxidant production and the production of reactive oxygen species (ROS). Leydig cells have a high content of PUFAs in their cell membrane, making it easy to bind ROS. Most natural antioxidants are found in plants, including Moringa. In this work, aged Wistar rats' Leydig cells will be used to test the antioxidant activity of an ethanol extract from the leaves of Moringa oleivera (Rattus norvegicus). The study involved the division of 36 elderly rats, who were between the ages of 18 and 19 months, into two groups. For thirty days, the control group received the same quantity of 0.5% CMC every day, whereas the treatment group received 50 mg/kgBW/0.5 mL of Moringa leaf ethanol extract daily. The rats were healthy and free of physical impairments. The Independent Samples T-Test is used to assess the data in order to find any variations between the treatment and control groups. The significant difference (p < 0.00) in Leydig cell counts between the extract-treated group and the control group suggests that the ethanol extract of Moringa leaves can have a major effect on the number of Leydig cells in Old Wistar rats (Rattus Norvegicus).